Integrating multi-criteria decision making and public sentiment analysis for sustainable urban green space planning - Muhammad Syafaat S. Kuba; Muhammad Faisal; Nurnawaty Nurnawaty; Titik Khawa Abdul Rahman; Andi Makbul Syamsuri; Muhyiddin AM Hayat; Rizki Yusliana Bakti (Bulletin of Electrical Engineering and Informatics, 2026)
Sustainable planning of green open spaces (GOS) requires decision-making models that combine expert evaluation with public input. This study proposes a novel hybrid framework that integrates multi-criteria group decision making (MCGDM) with public sentiment analysis to support community-based and data-driven urban planning. The workflow consists of evaluating 25 community-proposed GOS locations using stepwise weight assessment ratio analysis (SWARA) for criteria weighting and MABAC-BORDA for multi-criteria ranking, resulting in 11 feasible alternatives. To incorporate community perspectives, a term frequency-inverse document frequency-support vector machine (TF-IDF–SVM) classifier was applied to 1500 public comments, where SVM achieved the highest accuracy (0.80–0.96). The integrated approach improves ranking stability, reduces decision ambiguity, and strengthens alignment between expert judgment and community sentiment. This study contributes a transparent, participatory decision-support model that unifies MCGDM and sentiment analysis to enhance the effectiveness of sustainable GOS planning.